High‐Performance Composite Lithium Anodes Enabled by Electronic/Ionic Dual‐Conductive Paths for Solid‐State Li Metal Batteries - Yang, Zuguang; Li, Min; Lu, Guanjie; Wang, Yumei; Wei, Jie; Hu, Xiaolin; Li, Zongyang; Li, Penghua; Xu, Chaohe (Small (Weinheim an der Bergstrasse, Germany), 2022)
Solid‐state lithium metal batteries (SSLMBs) promise high energy density and high safety by employing high‐capacity Li metal anode and solid‐state electrolytes. However, the construction of the composite Li metal electrode is a neglected but important subject when the extensive research focuses on the interface between the solid electrolyte Li6.4La3Zr1.4Ta0.6O12 and Li metal anode. Here, an electronic–ionic conducting composite Li metal anode consisting of Li–Al alloy and LiF is constructed to achieve the stable electronic–ionic transport channel and the intimate interface contact, which can realize the uniform Li deposition and the efficiency utilization of lithium in composite Li metal electrode. Therefore, the symmetric battery with composite Li metal electrode exhibits the high critical current density with 1.2 mA cm−2 and stable cycle for 1500 h at 0.3 mA cm−2, 25 °C. Moreover, the SSLMBs matched with LiFePO4 and LiNi0.8Co0.1Mn0.1O2 achieve the outstanding electrochemical performance, verifying the feasibility of composite Li metal electrode in various SSLMBs systems. The electronic–ionic conducting composite Li metal anode consisting of Li–Al alloy and LiF is constructed, which can establish the stable electronic–ionic transport channel enhancing the utilization efficiency of internal lithium in Li metal electrode, promoting the homogeneous Li metal deposition, as well as improving the wettability of molten Li.